At-scale delivery of Essential Nutrition Interventions (ENIs) in India is limited by variable gaps in policy, design, implementation and demand - Avula, Rasmi; Kim, Sunny S.; Kohli, Neha; Chakrabarti, Suman; Tyagi, Parul; Singh, Kavita; van den Bold, Mara; Kadiyala, Suneetha; Menon, Purnima (Wiley, 2015)
Evidence suggests that increasing coverage of 14 ENIs from pre‐pregnancy to early childhood can reduce maternal and child undernutrition. In India, less than 55% of women and children receive any of the ENIs. We assessed readiness to achieve at‐scale delivery of ENIs through an analysis of policies, programs, intervention design, implementation, monitoring and service use. Policy guidance and program design were examined through content analysis. We studied provision of and demand for ENIs in two states ‐ Odisha & Madhya Pradesh, using primary data collection [a survey of frontline workers (FLW) (N=1140) and households with children aged 0‐2 y (N=2300) in 3 districts per state; semi‐structured interviews with officials and health workers at multiple levels]. Evidence‐based policies and operational guidelines exist for most ENIs but not monitoring indicators; gaps exist for community‐based management of acute malnutrition (CMAM) and nutritional care during illness. Limited implementation experience exists for many ENIs, particularly for counseling of complementary feeding, pediatric anemia control and CMAM. FLW knowledge and role clarity are also weak for these ENIs. Less than 1/3 of mothers got infant feeding advice during FLW home visits; receipt of information on pediatric anemia and awareness about use of iron supplements were also low, reflecting demand challenges. Despite policies and program guidelines, scale up of ENIs in India is limited by gaps in operational guidance, monitoring indicators, unclear FLW roles and low service demand. Funding: Bill & Melinda Gates Foundation, through POSHAN, led by IFPRI